How game–project learning enhances creative thinking in elementary geometry? - Anton Prayitno; Abdul Hamid; Nanik Sulistiyah (Institute of Advanced Engineering and Science, 2026)
The rapid advancement of technology and the demands of 21st-century competencies require mathematics instruction to move beyond procedural learning toward strengthening students’ creative mathematical thinking. However, elementary students’ creative thinking remains low, particularly in geometry problem solving. Although gamification and project-based learning (PjBL) have shown positive effects, empirical studies integrating both approaches to foster creative mathematical thinking in elementary geometry are still limited. This study examined the effect of game–project-based learning (GPBL) on fifth-grade students’ creative mathematical thinking in geometric problem solving. A quantitative quasi-experimental pretest–post-test control group design was employed involving 84 students assigned to an experimental group and a control group. The experimental group received GPBL supported by game and project activities, while the control group received direct instruction. Data were collected using a creative mathematical thinking test and analyzed using repeated measures analysis of variance (ANOVA). The results showed significantly greater improvement in the experimental group than in the control group, indicated by significant time effects, a significant time×group interaction, and significant between-group differences with medium-to-large effect sizes. These findings suggest that GPBL promotes progressive concept exploration and encourages solution strategies. Therefore, GPBL can be integrated into elementary geometry instruction to foster students’ creative mathematical thinking.